THE RELEVANCE OF THE TAISIRUL KARIMIR RAHMAN COMMENTARY TO STRENGTHENING SYNERGY BETWEEN PARENTS AND EDUCATORS IN ISLAMIC RELIGIOUS EDUCATION - Fikri Maulyda; Enjang Burhanudin Yusuf (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze the educational concepts presented in Taisir al-Karim ar-Rahman, the Qur’anic exegesis of Shaykh Abdurrahman bin Nasir As-Sa’di, and to examine their relevance to strengthening the synergy between parents and educators in Islamic Religious Education (PAI). The study is motivated by the insufficient integration of Islamic values between home and school environments, which often results in discontinuity in students’ religious internalization. Employing a qualitative approach through library research, this study examines As-Sa’di’s exegetical ideas and supports them with empirical studies on family–school collaboration. The findings indicate that As-Sa’di emphasizes two foundational pillars of Islamic education: the family as the primary institution responsible for instilling faith and moral character, and the educator as the guide who reinforces religious knowledge and teaches with wisdom. The synergy between these two pillars is viewed as a critical prerequisite for the success of Islamic education, particularly in curricula that balance the components of faith, worship, ethics, and social conduct. This study concludes that the synergy model derived from As-Sa’di’s tafsir offers a strong normative framework for developing holistic and character-oriented Islamic education.